The evaluation of a behavioural intervention to reduce the impact of indoor air pollution on child respiratory health - Barnes, Russel Brendon (My University, 2008)
ABSTRACT Indoor air pollution has been associated with acute lower respiratory infections amongst children less than five years old in developing countries. Very little is known about the potential role of behavioural change in reducing child indoor air pollution exposure. This thesis explores three questions: did people change their behaviours following exposure to an intervention that promoted the health benefits of behavioural change? Were changes in behaviour attributable to the intervention? What were the motivations and barriers to behavioural change? The evaluation included a quantitative and a qualitative study. The quantitative study utilised a quasiexperimental before-after design amongst an intervention village (n=98 households). Results were compared to a similar control village (n=121) that did not receive the intervention. Baseline data were collected during winter 2003 and follow-up data were collected during winter 2004 (12 months later). A qualitative evaluation, using two rounds of 4 focus group interviews each, was used to answer questions that emerged from the quantitative study. Indoor air quality - PM10, CO and CO (measured on the youngest child) - were measured over a 24 hour period in randomly selected households before and after the intervention in the intervention (n=36) and control (n=38) groups. After adjusting for confounding factors, there was no statistical association between having the received the intervention and the likelihood of burning outdoors at follow-up (OR=1.16; 95% CI 0.6-1.8). Indoor air quality data showed significant median reductions in PM10 (94-96%), CO (85-97%) and CO (child) (83- 95%) amongst households that burned outdoors compared to those that burned indoors. Results from the qualitative study suggest that motivations for outdoor burning included: health considerations, reaction to participating in the study, reduced drudgery and prestige. Barriers to outdoor burning included the need for space heating during winter, perceptions of low indoor air pollution risk and gender relations. This study highlights the potential for exposure reduction through behavioural change and is original for three reasons. It is the first behavioural intervention study designed to reduce indoor air pollution in a rural African setting. Secondly, it is the first intervention study in the indoor air pollution field to identify the factors that influenced behavioural change. Thirdly, it is one of the first studies to align debates about behavioural change in the field of indoor air pollution with those in the broader environmental health promotion literature.
Keywords: indoor air pollution; behavioural intervention; developing countries